Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah Pada UMKM Warung Sarapan Pagi Supiah Kecamatan Limapuluh Pekanbaru - Dwi Suci Arlita; Intan Putri Azhari; Rama Gita Suci (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to find out how the application and solutions in Financial Accounting Standards for Micro, Small and Medium Entities in MSMEs, Supiah Breakfast Stalls, Limapuluh District, Pekanbaru. The research method used is descriptive qualitative. The data sources used are primary data and secondary data. Research informants are business owners and cashiers. Data collection techniques are observation, interviews and documentation. Data analysis techniques data reduction, data presentation and conclusion. To test the validity of the data using triangulation. The results of this study show that, the recording of financial statements made by MSMEs Warung Breakfast Pagi Supiah has not implemented SAK-EMKM, this is due to the lack of knowledge of business actors about SAK-EMKM. The preparation of the statement of financial position carried out only sums between cash in and cash out and the income statement obtained from income minus the expenses incurred, So that the information presented regarding assets, liabilities, income and financial expenses is only recorded simply and manually. Solutions in the application of SAK-EMKM In MSMEs Warung Breakfast Pagi Supiah, the cooperative office conducted socialization on the preparation of SAK-EMKM financial statements per sub-district, with the existence of good and correct financial statements that will help business actors in supporting business development.